Properties of cheese and ground beef in the presence of staghorn sumac. Issue 2 (10th March 2023) - Wang, Sunan; Nie, Shaoping; Gan, Ren‐You; Zhu, Fan
Abstract: Cost‐effective and under‐exploited plant species as functional food ingredients represent alternatives to chemicals with safety concerns and potent toxicity. Staghorn sumac ( Rhus typhina ) is considered a good source of natural polyphenols, which can be introduced into food products to carry out some specific technological functions (e.g., antioxidation and preservation). However, sumac fruit as a spice is under‐explored for its diversified uses in various food products as a novel functional ingredient. This study explored the technological feasibility and sensory acceptability of two representative sumac‐fortified food systems, namely Cheddar cheese and ground beef. Extracts of sumac (0.5%−5%) dose‐dependently increased the total phenolic and anthocyanin contents, while reducing thiobarbituric acid reactive substance (up to 46%), total plate counts of bacteria (up to 4.5 log colony‐forming units [CFU]/g) and pH of the cheese. In fresh ground beef, sumac extract at concentrations of 1%−5% was effective in reducing the total aerobic counts of Escherichia coli inoculated fresh ground beef by 0.16−1.14 log CFU/g, while improving meat color and oxidative stability during a storage period of 7 days at 4°C. Phytochemical profiling by high‐performance liquid chromatography showed the presence of gallic acid, caffeic acid, ellagic acid, quercetin and anthocyanins in the sumac extracts. These compounds were possibly responsible for the antimicrobial and antioxidant activities in the evaluated food systems. Sensory acceptability of Cheddar cheese or cooked beef meatballs with sumac extract addition (0.5%−3%) were similar to their respective controls. This study provides a feasible approach to satisfy health‐conscious consumers who favor a natural multifunctional ingredient to preserve food products. Abstract : Staghorn sumac fruit as a spice is under‐explored for its diversified uses in various food products as a novel functional ingredient. This study explored the technological feasibility and sensory acceptability of two representative sumac‐fortified food systems, namely Cheddar cheese and ground beef. This study provides a feasible approach to satisfy health‐conscious consumers who favor a natural multifunctional ingredient to preserve food products.